Interactive Horror Story Games and Its Core Drive Implementations: Case Study on The Dark Pictures Anthology Season One Games - Galih Dea Pratama; Andien Dwi Novika (Journal of Games, Game Art, and Gamification, 2023)
In presenting immersive gameplay experience to its base of players, various game titles provide certain game techniques in its disposal. As in The Dark Pictures Anthology games, the series provides branching narrative to add the layers of challenge given to the player. In order to persuade the player to complete the game, there are Core Drives which embody the player’s motivation throughout the game itself. In this research, we will present how the Core Drives are represented in interactive horror story games through the experiment on The Dark Pictures Anthology Season One games with analysis on the Core Drives using Octalysis framework. The experiment shows that the game series brought many game techniques, with Narrative, Progress Bar, Instant Feedback, alongside Plant-Poison Picker, Count Down Timer, Visual Grave, and Rightful Heritage becoming the prominent techniques from the series.